A conceptual framework for measuring the acceptance of pervasive learning - Koondhar, Muhammad Yaqoob; Abdul Molok , Nurul Nuha; Chandio, Fida Hussain; Rind, Muhammad Malook; Raza, Ali; Shah, Asadullah (2015)
The technology innovation and advancements in smart phones and wireless communications have reformed learning techniques such as Pervasive Learning (P-Learning), Mobile Learning (M-Learning) and Electronic Learning (E-Learning). P-Learning is the new form of innovative technologies for learning that occurs at the user's will at anywhere, anytime and with any mobile or handheld devices. Students using P-Learning can overcome the obstacles such as poor facilities in the classrooms, gender, culture and religious barriers, hectic personal and professional lives by providing flexibilities and more than one medium for learning. This research is intended to study the specific factors influencing students as to whether accept and use these new technologies (P- learning). This study extends the existing research on Technology Acceptance Model (TAM) and will develop an integrated model of P-Learning acceptance. It is also expected that this research study will help provide strategies for educators in the development and implementation of courses designed to integrate technology. This study employs mixed research methods for triangulation to get the desired research results. The data for the research is collected through focus groups and cross sectional questionnaire survey.